Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan, dan Tingkat Penghasilan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Bandung - Wulandari; Saepuloh, Cepi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The number of motorcycle users continues to increase every year in West Java, but in fact there are still many taxpayers who no longer re-register their vehicles, especially in Bandung City. This study aims to determine the effect of taxpayer awareness, service quality, and income level on motor vehicle taxpayer compliance in Bandung City partially. This research is a quantitative research with descriptive approach. This study used a questionnaire method to collect data with a sample of 100 respondents from the total population of motor vehicle owners in the last year of 1.562.668. The data analysis techniques used in this study are Descriptive Analysis, Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, Correlation Coefficient Test, Determination Test (R2), t test, and F test. The results of the research conducted show that taxpayer awareness has a positive and significant influence on taxpayer compliance, then service quality has a positive and significant influence on taxpayer compliance, and income level has a positive and significant influence on taxpayer compliance.